Plant pruning and fold of the main stem in the formation of clonal coffee - Schmidt, Raquel; Machado Dias, Jairo Rafael; Curitiba Espindula, Marcelo; Partelli, Fábio Luiz; Romeiro Alves, Erilene (Coffee Science - ISSN 1984-3909, 2015)
This study aimed to evaluate the vegetative growth of Coffea canephora undergoing techniques of cut tip bending the main stem at different times. We used the design in randomized blocks, factorial 2 (technical) x 5 (60, 75, 90, 105 and 120 days after planting the crop) with four replicates. Induction of clonal coffee should be done at 60 and 86 days after permanent planting, utilizing the bending and the apical trimming, respectively. The bending of the main stem of the coffee clonal promotes superior performance in the induction of shoots.